2018
DOI: 10.1007/s10552-018-1077-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer incidence among Hispanics and non-Hispanic Whites in the United States

Abstract: Opposing incidence trends in younger versus older Hispanics may reflect generational differences in CRC risk by birth cohort, as well as environmental exposures and lifestyle-related risk factors associated with immigration and acculturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Nationwide data has shown that similar to African-Americans, the proportion of Hispanic/Latinos diagnosed with CRC younger than age 50 is nearly double the rate seen in Whites (12% vs. 6.7%) ( Figure 2 ) [ 32 ]. However, Hispanic/Latinos have lower overall CRC incidence than Whites across all age groups, including for individuals younger than 50 [ 40 , 41 , 42 ].…”
Section: Early-onset Crc Epidemiology and Disparitiesmentioning
confidence: 99%
“…Nationwide data has shown that similar to African-Americans, the proportion of Hispanic/Latinos diagnosed with CRC younger than age 50 is nearly double the rate seen in Whites (12% vs. 6.7%) ( Figure 2 ) [ 32 ]. However, Hispanic/Latinos have lower overall CRC incidence than Whites across all age groups, including for individuals younger than 50 [ 40 , 41 , 42 ].…”
Section: Early-onset Crc Epidemiology and Disparitiesmentioning
confidence: 99%
“…Currently, Hispanics are the largest and one of the fastest growing minority populations in the U.S. (United States Census Bureau, 2019a; United States Census Bureau, 2019b). While CRC incidence and mortality have decreased in all racial and ethnic groups over the past two decades, the decline has been less notable for Hispanics (Ashktorab et al, 2017;Ellis et al, 2018;Garcia et al, 2018). Mortality from CRC dropped by 15.1% among non-Hispanic Whites from 2000 to 2011 but by only 5.9% among Hispanics (Barzi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CRC rates among Hispanics are lower than those among non-Hispanic Whites and African Americans, with African Americans having the highest rate among both sexes (Noone et al, 2017; Siegel et al, 2015). National data indicate that CRC incidence is decreasing among Hispanics; however, it is more common for Hispanics younger than 50 years old to be diagnosed and this incidence rate is higher than that for non-Hispanic White and African Americans (ACS, 2015, 2018; Garcia, Pruitt, Singal, & Murphy, 2018; Jackson, Oman, Patel, & Vega, 2016; Jafri, Gould, El-Serag, Duan, & Davila, 2013; Koblinski, Jandova, & Nfonsam, 2018). CRC incidence is higher in Hispanic males than females, yet it is the third leading cause of cancer death among both genders (ACS, 2015; Koblinski et al, 2018; Siegel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%